Spatial strategic use as performance indicator in racket and wall sports - J. I. Alonso; F. Argudo (Asociación Española de Ciencias del Deporte, 2010)
A computerized system of neuronal networks was used as a performance indicator to go deeply into the spatial strategic use within the racquet and wall sports. The aim of this investigation was: a) to determine the influence of the players' position in the court when finishing the point and b) to determine if there is any relation between the spaces where the ball is sent to, the game walls and its performance. . We recorded 1226 points in male category and analysed their final action. Specific software was designed for the two-dimensional analysis of the images and the management of the data. We carried out a period of training with four observers for four weeks keeping in mind aspects dealt with by several authors on the necessary and adequate training of the observers adapted to the management of the already described observation tool The final action that hit front wall number 3 always caused displacement, confirming us other data already mentioned. For level 1 we find that the most related spaces to efficacy are front wall 1, side wall 1 and 3, and court 1. We observed the tendency that shows the results where the final action is more efficient than the impact on the two extreme areas of the court and side wall. Key Words: Spatial strategic use, performance indicators, racquet and wall sports.